450 Patents – The Key Is Not the Number, It's the Process: Prof. Lebby: "Bring Photonics companies together to agree on road maps". Issue 4 (1st August 2019) - Pozo, Jose
Abstract: Michael Lebby, renowned entrepreneur, academic, and inventor with more than 450 utility patents to his name, talks to EPIC about the past, present, and future of photonics.